Required Steps of Managing International Equity Placement Strategic Alliance - Wandebori, Harimukti; de Bruijn, Erik Joost; Steenhuis, Harm-Jan (School of Business and Management Institut Teknologi Bandung, 2011)
The purpose of the research is to unravel the steps of managing international equity placement strategic alliance (IEPSA). The steps of managing an IEPSA are obtained by conducting theoretical review. The theoretical reviews consist of theory of strategic alliance; definition, classification, and finding definition of an IEPSA, political and analytical considerations and the necessary steps. These steps of managing IEPSA can be classified into analyzing of macro consideration, micro consideration, domestic company’s stakeholder support, cultural understanding, strategic planning, internal support, human resource management, organizational arrangement, management control system, evolved cultural understanding, and evaluating results. In this research, the domestic partners who formed the IEPSAs are limited to State-Owned Enterprises (SOEs). The IEPSA was one of the means of privatization. The research will be beneficial for both foreign and domestic partners who form an IEPSA in the previous SOEs. By knowing the steps of managing the IEPSA both partners will be able to secure a successful implementation of IEPSA. By identifying the steps of managing the IEPSA, the stakeholder will not see IEPSA as threat rather as an opportunity to improve performance, to create synergy, and generate benefits for both partners and stakeholder. By knowing the necessary steps of managing the IEPSA, the stakeholder including society and politician will envisage the IEPSA as a means of effectively improving the SOEs’ performances.The research was espected to provide contributions for the research on strategic alliances. Apparently, there exist no literatures discussing about IEPSA in the domain of strategic alliances. Keywords: strategic alliance, equity placement, international equity placement strategic alliance, privatization, steps of international equity placement strategic alliance, state-owned enterprises